Establishing a National Hydrographic Service with United Nations Technical Co-Operation - Holden, Graham J. (The International Hydrographic Review, 2015)
The Report of the Group of Experts on Hydrographic Surveying and Nautical Charting, published by the United Nations Economic and Social Council in 1978 [1], advised developing countries to examine the need for hydrographic services and to ascertain what aid they could expect from the United Nations in establishing a national hydrographic service. This paper deals with certain aspects of the Report, explains, in general terms, the financial and technical assistance which may be provided and the United Nations agencies which may be involved. The concept of a UN-assisted project is discussed and its application in the planning of a hydrographic project is explained. A case study of a hydrographic project with United Nations Technical Co-operation, in which the author is involved, is presented to give some indication of the time scale involved, the problems which may be encountered and methods of solving them. The paper begins with the assumption that the Government of a developing country has realised the need to establish a hydrographic service and has identified the department to run it. It presents no arguments for or against such a decision but aims to give some insight into the formulation of a hydrographic project with United Nations Technical Co-operation.